Early considerations for a transport system in the Gaza Strip: A short-term, sustainable mobility proposal - Giuffrida, Nadia; Viscio, Salvatore; Binetti, Mario; Ottomanelli, Michele (Plurimondi; No 22 (2025): War and peace, 2025)
This paper presents early considerations for a short-term, sustainable transport strategy for the Gaza Strip, developed using the Dar Al Omran – Rasem Badran Master Plan as a long-term spatial framework. Given the urgent need for rapid, low-cost mobility solutions that can support reconstruction while ensuring social inclusion, the proposed system integrates multiple modes, including Bus Rapid Transit (BRT), community taxis, active mobility infrastructure, and shared mobility services. Five key mobility hubs—Beit Hanoun, Gaza City, Deir al-Balah, Khan Yunis, and Rafah—serve as structural anchors for a scalable network. Two alternative BRT configurations are examined. These options are complemented by feeder services, cycling facilities, and innovative shared mobility solutions such as cargo bikes and drone-enabled deliveries. The proposal emphasizes the importance of coordinated land use–transport integration to ensure that mobility interventions respond to community needs and adapt as new data becomes available. Overall, the proposal offers a pragmatic path from immediate recovery to long-term, resilient urban mobility development in the Gaza Strip.